Modeling of Colorado Learning Attitude Science Survey in Indonesian Version: A Study with Applying Item Response Theory - Mutmainna, Mutmainna; Hasyim, Mutahharah; Syamsuriwal, Syamsuriwal; Setiaji, Bayu; Setiawati, Farida Agus (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2024)
Colorado Learning Attitudes about Science Survey (CLASS) is an instrument designed to explore students' perceptions of physics and assess how closely their beliefs correspond with those of professional physicists. Before the development of CLASS, several similar instruments were developed in the field of Physics Education such as the Maryland Physics Expectation (MPEX), Views About Science Survey (VASS), and Epistemological Beliefs Assessment for Physical Science (EBAPS). Adams et al. developed CLASS in 2006 by evaluating these three instruments. Since then, CLASS has been extensively studied for its use in research, especially in the field of Physics Education, and has also been applied in other fields and translated into several languages. As a form of community strengthening, this article attempts to report the research findings related to the use of the CLASS instrument that has been translated into Indonesian. A total of 292 undergraduate students were sampled in this study, who are students from four universities. The respondents in this study were students who had enrolled in the Fundamental of Physics course. The data obtained were analysed with Item Response Theory (IRT) for the polytomous scale. There are Grade Response Model (GRM), Partial Credit Model (PCM), Rating Scale Model (RSM), and Generalized Partial Credit Model (GPCM). The research results show that among the four models of approach and based on the criteria used, the model considered most suitable is GRM. The research also shows that the number of items declared consistent with the model does not cover all CLASS items but rather some items. This finding indicates that further exploration is needed regarding the CLASS instrument items, especially in the Indonesian version. The findings of this study also add to the wealth of knowledge related to the quality assessment of the CLASS instrument through the modern test theory approach (IRT). Thus, the CLASS instrument can be regarded as a standard instrument and can be used globally across various populations.